ANALISIS MANAJEMEN MODAL KERJA PADA UMKM WARUNG KITSCH DI KABUPATEN LUMAJANG - Umi Aimmatun Nadziroh; Raisya A Yasmin; Dinda Intan Pratiwi; Sulton Sholehuddin; Mohamad Bastomi (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
A company's working capital comes from the company's cash flow, which is used for its operations. The working capital of a company must always be circulating in order for the company to operate well and to grow. Although research on working capital management is not as extensive as research in the field of capital and long-term investments, proper working capital is a necessary condition for the success of a company, especially for small businesses. This research uses a qualitative descriptive research method. Qualitative descriptive method adapts the opinions between the researcher and the informant. This method was chosen because the analysis cannot be in numerical form and the researcher more clearly describes all the phenomena in society. Analysis of Working Capital on company growth has an important role for a company because the amount and size of working capital usage in operational activities is very important to be managed so that the size of working capital is balanced with the profit earned by the company. Based on the research conducted on SME Warung Kitsch, the conclusion that can be drawn from this discussion is that Warung Kitsch must provide funds of around Rp 9,482,737,- in its business cycle with a working capital period of 14 and 11 days and a daily cost of 486,067.